2014
DOI: 10.1007/s10608-014-9656-2
|View full text |Cite
|
Sign up to set email alerts
|

Are Social Comparisons Detrimental for the Mood and Self-Esteem of Individuals with an Affective Disorder?

Abstract: The current study tested whether experimentally induced social comparisons affect mood and self-esteem in euthymic unipolar and bipolar patients, compared to participants without any history of affective disorders. It was predicted that unfavourable upward comparisons with feedback that another person was performing better would have a negative effect on implicit self-esteem and explicit mood (positive and negative affect) in unipolar patients. We further predicted that favourable downward social comparisons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…These findings are in line with research indicating that upward social comparison can be experienced in a negative way (Buunk & Gibbons, 2007) that increases negative affect (Fuhr, Hautzinger, & Meyer, 2015). Our findings are also in line with research indicating that anticipation of guilt feelings for letting other people down may lead individuals to avoid forming interdependent partnerships with people they see as more competent than themselves (Wiltermuth & Cohen, 2014).…”
Section: Effect Of the Coplayer Rank On Emotional And Behavioral Resp...supporting
confidence: 92%
“…These findings are in line with research indicating that upward social comparison can be experienced in a negative way (Buunk & Gibbons, 2007) that increases negative affect (Fuhr, Hautzinger, & Meyer, 2015). Our findings are also in line with research indicating that anticipation of guilt feelings for letting other people down may lead individuals to avoid forming interdependent partnerships with people they see as more competent than themselves (Wiltermuth & Cohen, 2014).…”
Section: Effect Of the Coplayer Rank On Emotional And Behavioral Resp...supporting
confidence: 92%
“…Experimental paradigms within clinical studies are severely lacking, yet the findings here provide some support for observational studies with regard to affective reactions and the relevance of comparison salience. The two experiments appear to contradict each other with regard to differences between depression groups and controls; however, the comparison dimensions differed, where Buunk and Brenninkmeijer (2001) focused on mental health, which could be considered more salient to a depressed sample than environmental concerns used by Fuhr et al (2015). This suggests that the salience of the comparison dimension may determine how individuals evaluate and react to SC information, as well as general interest in SC (e.g., SCO), which implicates individual differences at the stage of acquiring SC information.…”
Section: Resultsmentioning
confidence: 90%
“…Fuhr, Hautzinger, and Meyer (2015) experimentally induced upward or downward SC in outpatients with a lifetime diagnosis of major depression and healthy controls. The paradigm used a manipulated computer‐based brainstorming task for generating ideas to protect the environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manipulation check indicated that these instructions were followed, as participants in the stretching condition indicated comparing themselves with other group members. To the extent that the stretching participants evaluated themselves against group members with a downward social comparison style, they may have had more positive affect (Fuhr et al, 2015) and less reactivity to the dysphoric stressor.…”
Section: Discussionmentioning
confidence: 99%